Neotethyan subduction ignited the Iran arc and back-arc differently - Shafaii Moghadam, H. (2020)
Most arcs show systematic temporal and spatial variations in magmatism with clear shifts in igneous rock compositions between those of the magmatic front (MF) and those in the backarc (BA). It is unclear if similar magmatic polarity is seen for extensional continental arcs. Herein, we use geochemical and isotopic characteristics coupled with zircon U‐Pb geochronology to identify the different magmatic style of the Iran convergent margin, an extensional system that evolved over 100 Myr. Our new and compiled U‐Pb ages indicate that major magmatic episodes for the NE Iran BA occurred at 110–80, 75–50, 50–35, 35–20, and 15–10 Ma. In contrast to NE Iran BA magmatic episodes, compiled data from MF display two main magmatic episodes at 95–75 and 55–5 Ma, indicating more continuous magmatism for the MF than for the BA. We show that Paleogene Iran serves as a useful example of a continental arc under extension. Our data also suggest that there is not a clear relationship between the subduction velocity of Neotethyan Ocean beneath Iran and magmatic activity in Iran. Our results imply that the isotopic compositions of Iran BA igneous rocks do not directly correspond to the changes in tectonic processes or geodynamics, but other parameters such as the composition of lithosphere and melt source(s) should be considered. In addition, changes in subduction zone dynamics and contractional versus extensional tectonic regimes influenced the composition of MF and BA magmatic rocks. These controls diminished the geochemical and isotopic variations between the magmatic front and backarc.